Ta-C composite coating and preparation method thereof
By preparing a Ta-C composite coating on the compressor blades, the problem of easy peeling of the coating was solved, and the effects of high bonding strength, low friction coefficient and high wear resistance were achieved, thereby improving the wear resistance and life of the compressor parts.
Patent Information
- Application Number
- CN202511213334.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-28
- Publication Date
- 2025-10-10
AI Technical Summary
Existing compressor blade coatings are prone to peeling off during high-speed movement and have insufficient bonding strength. In addition, traditional DLC coatings have high hardness but poor bonding strength with the substrate, resulting in insufficient wear resistance and lifespan.
Ta-C composite coating, including transition layer and wear-resistant layer, is used. Me layer, MeN layer, Me(W)N layer, MeWN layer, WC layer, WC/Ta-C composite layer and Ta-C layer are deposited on the substrate by magnetron sputtering and arc ion plating process. Combined with plasma nitriding treatment, the composite coating structure is optimized to improve bonding strength and hardness.
It enhances the bonding force between the substrate and the composite coating, improves the hardness, shear strength and wear resistance of the coating, reduces the friction coefficient and extends the service life of components.
Smart Images

Figure CN120758848A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of coating, in particular to a Ta-C composite coating and a preparation method thereof. BACKGROUND
[0002] With the continuous improvement of the power of the compressor, the operating conditions of the compressor become increasingly harsh, and higher requirements are put forward for the wear resistance, reliability and service life of the compressor parts, especially the crankshaft parts rotating at high speed and the blades reciprocating at high speed inside the compressor.
[0003] Taking the blade part as an example, the reciprocating operation of the blade in the currently produced high-power compressor can be as high as 7200 times per minute, the pressure difference in the working cavity is greatly increased, and the wear trend of the blade surface is more and more obvious. The wear failure modes mainly include adhesive wear in the initial biting stage (stage I of the Streebel curve) and fatigue wear in the later fatigue stage (stage III of the Streebel curve). Therefore, the low friction coefficient, good adhesion and high wear resistance of the blade surface coating are crucial. The low friction coefficient can slow down the adhesive wear in the biting stage, and the excellent adhesion and high wear resistance can significantly reduce the fatigue wear of the coating and prolong the service life of the coating.
[0004] The commonly used coating for the blade in the high-power unit is a hydrogen-containing diamond-like carbon coating (H-DLC), which has very high hardness, excellent wear resistance, and very high coating deposition precision, which can ensure the dimensional accuracy and geometric tolerance of the parts. However, at the same time, because the hardness of DLC is high, the adhesion between the coating and the substrate has always been a challenge. Usually, the stainless steel substrate is subjected to gas nitriding treatment, but the white layer above the nitriding layer is brittle, which greatly affects the adhesion between the substrate and the coating, and easily causes the peeling of the coating during high-speed movement of the blade.
[0005] It should be noted that the information disclosed in the above background section is only used to strengthen the understanding of the background of the present application, and therefore can include information that does not constitute prior art known to those skilled in the art. SUMMARY
[0006] In view of the problems in the prior art, the purpose of the present application is to provide a Ta-C composite coating and a preparation method thereof. The composite coating has greater hardness, shear strength and wear resistance, and the surface still maintains a low friction coefficient. The new type of coating is introduced to improve the wear resistance and service life of the parts.
[0007] Specifically, the application provides a Ta-C composite coating formed on a high-speed steel substrate, a stainless steel substrate or a cast iron substrate, the composite coating comprising a transition layer and a wear-resistant layer arranged in sequence.
[0008] The transition layer comprises a Me layer, a MeN layer, a Me(W)N layer and a MeWN layer.
[0009] The wear-resistant layer comprises a WC layer, a WC / Ta-C composite layer and a Ta-C layer.
[0010] According to some examples of the application, in the thickness direction of the composite coating, the W content of the Me(W)N layer gradually increases.
[0011] According to some examples of the application, in the thickness direction of the composite coating, the W content of the Me(W)N layer gradually increases from 0% to (70±5)%; and / or
[0012] The W content of the MeWN layer is (70±5) %.
[0013] According to some examples of the application, the thickness of the transition layer is 35-45% of the thickness of the composite coating; and / or
[0014] The thickness of the Me layer is 5-10% of the thickness of the composite coating; and / or
[0015] The thickness of the MeN layer is 5-15% of the thickness of the composite coating; and / or
[0016] The thickness of the Me(W)N layer is 15-25% of the thickness of the composite coating; and / or
[0017] The thickness of the MeWN layer is 5-15% of the thickness of the composite coating.
[0018] According to some examples of the application, in the thickness direction of the composite coating, the content ratio of Ta-C to WC of the WC / Ta-C composite layer gradually increases.
[0019] According to some examples of the application, in the thickness direction of the composite coating, the content ratio of Ta-C to WC of the WC / Ta-C composite layer increases from 1 / 9 to 9.
[0020] According to some examples of the application, the thickness of the wear-resistant layer is 55-65% of the thickness of the composite coating; and / or
[0021] The thickness of the WC layer is 10-15% of the thickness of the composite coating; and / or
[0022] The thickness of the WC / Ta-C composite layer is 15-25% of the thickness of the composite coating; and / or
[0023] The thickness of the Ta-C layer is 20-30% of the thickness of the composite coating; and / or
[0024] SP in the WC / Ta-C composite layer or the Ta-C phase in the Ta-C layer 3 The carbon content ranges from 60% to 80%.
[0025] According to some examples of the present invention, the thickness of the composite coating is 3-4 μm.
[0026] The present invention also provides a method for preparing a Ta-C composite coating, which is suitable for preparing the aforementioned Ta-C composite coating, and comprises the following steps:
[0027] Providing a substrate, and sequentially depositing a Me layer, a MeN layer, a Me(W)N layer, a MeWN layer, and a WC layer on the substrate by a magnetron sputtering process;
[0028] The WC / Ta-C composite layer was deposited using magnetron sputtering technology;
[0029] The Ta-C layer was deposited using an arc ion plating process.
[0030] According to some examples of the present invention, before the step of depositing the Me layer, the preparation method further includes:
[0031] The substrate is treated by a plasma nitriding process to form an ion nitriding layer on the surface of the substrate.
[0032] Compared with the prior art, the Ta-C composite coating of the present invention adopts a composite gradient transition layer technology to optimize the structure of the composite coating as a whole, thereby improving the bonding force between the substrate and the composite coating and the interlayer bonding force of the composite coating, and enhancing the hardness, shear strength and wear resistance of the composite coating, while maintaining a low friction coefficient on the surface. By introducing this new structure of the coating, the wear resistance and life of the parts are improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The accompanying drawings, which are incorporated herein and constitute part of this specification, illustrate embodiments consistent with the application and, together with the description, further serve to explain the principles of the application. Other features, objects, and advantages of the application will be apparent from the detailed description of non-limiting embodiments that follows, when read in connection with the accompanying drawings. It will be apparent to one skilled in the art that the drawings described below are only illustrative of some embodiments of the application and that additional drawings can be obtained from these drawings by one of ordinary skill in the art without paying creative effort. In addition, the drawings are only schematic and not necessarily drawn to scale. The same reference numerals in different drawings represent the same or similar functionality, and thus their repeated description will be omitted. Some of the block diagrams shown in the drawings are functional entities, which do not necessarily have to correspond to physically or logically independent entities.
[0034] Figure 1 A schematic diagram of a Ta-C composite coating according to an embodiment of the application;
[0035] Figure 2 A scanning electron microscope image of a Ta-C composite coating according to an embodiment of the application;
[0036] Figure 3 An energy dispersive spectroscopy image of a Ta-C composite coating according to an embodiment of the application in the thickness direction. DETAILED DESCRIPTION
[0037] The embodiments of the present application will be described in detail with specific reference to particular examples. It will be understood that the present application is not limited to these examples and that the following examples are provided to disclose the best mode of practicing the present application. The details of the application, both as to its organization and method of operation, can be obtained from the detailed description that follows, and by studying the illustrative embodiments described in the detailed description of the application. It will be understood that the present application is not limited to the embodiments described herein, which are presented as examples of the present application. Embodiments of the present application can be implemented in any device, system or method that is configured to perform the functions described herein. It will be understood that the application is not limited to the details of construction and the arrangement of components set forth in the following description or illustrated in the drawings. Also, it is understood that the application is not limited only to the particular examples described herein and that the application includes all alternatives falling within the spirit and scope of the application.
[0038] The embodiments of the present application will be described in detail with specific reference to particular examples. It will be understood that the present application is not limited to these examples and that the following examples are provided to disclose the best mode of practicing the present application. The details of the application, both as to its organization and method of operation, can be obtained from the detailed description that follows, and by studying the illustrative embodiments described in the detailed description of the application. It will be understood that the present application is not limited to the embodiments described herein, which are presented as examples of the present application. Embodiments of the present application can be implemented in any device, system or method that is configured to perform the functions described herein. It will be understood that the application is not limited to the details of construction and the arrangement of components set forth in the following description or illustrated in the drawings. Also, it is understood that the application is not limited only to the particular examples described herein and that the application includes all alternatives falling within the spirit and scope of the application.
[0039] In the description of the present application, the expressions "one embodiment", "some embodiments", "an example", "a specific example", or "some examples" are used to represent a particular feature, structure, material, or characteristic in at least one embodiment or example of the present application. Furthermore, the expressions "in one embodiment" or "in some embodiments" do not necessarily refer to the same embodiment or example; however, they can. Moreover, the expressions "in one embodiment" or "in some embodiments" are not necessarily mutually exclusive from other expressions such as "in another embodiment" or "in some other embodiments". The expressions "in one embodiment" or "in some embodiments" are merely used to describe different features, structures, materials, or characteristics of one or more embodiments or examples of the present application and are not necessarily mutually exclusive.
[0040] In order to clearly illustrate the present application, devices other than those that are essential to an understanding of the application are omitted, and like or similar components that are denoted by the same reference numerals throughout the drawings are given the same reference numerals.
[0041] Throughout the specification, when it is said that an element is "connected" to another element, this includes not only the case where it is "directly connected", but also the case where it is "indirectly connected" with other elements interposed therebetween. In addition, when it is said that an element "includes" a certain constituent element, other constituent elements are not excluded unless specifically stated to the contrary, but it means that other constituent elements can also be included.
[0042] When it is said that an element is "on" another element, it can be directly on the other element, but it can also be accompanied by other elements therebetween. When it is said in contrast that an element is "directly on" another element, there are no other elements therebetween.
[0043] Although the terms first, second, etc. can be used herein to describe various elements, these elements should not be limited by these terms. These terms are only used to distinguish one element from another. For example, a first interface and a second interface, etc. are denoted. Also, as used herein, the singular forms "a", "an" and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise. It will be further understood that the terms "comprises", "comprising", "includes" and / or "including" means that the mentioned features, steps, operations, elements, components, items, species, and / or groups are present, but do not exclude the presence or addition of one or more other features, steps, operations, elements, components, items, species, and / or groups. The terms "or" and "and / or" as used herein are to be interpreted as inclusive, i.e., as meaning one or any combination of items. Thus, "A, B or C" or "A, B and / or C" means "any of the following: A; B; C; A and B; A and C; B and C; A, B and C". This definition applies only when a combination of elements, functions, steps or actions is possible, and such a combination is inherently mutually exclusive.
[0044] The specific terminology used herein has been chosen by the inventors for reasons of readability and inclusivity, and is not intended to limit the scope of the application. Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. It will be further understood that terms, such as those defined in commonly used dictionaries, should be interpreted as having a meaning that is consistent with their meaning in the context of the relevant art and the present disclosure and will not be interpreted in an overly literal or overly formal sense unless expressly so defined herein.
[0045] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. It will be further understood that terms, such as those defined in commonly used dictionaries, should be interpreted as having a meaning that is consistent with their meaning in the context of the relevant art and the present disclosure and will not be interpreted in an overly literal or overly formal sense unless expressly so defined herein.
[0046] The Ta-C composite coating and the preparation method of the present application will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that each specific embodiment is not intended to limit the protection scope of the present application.
[0047] The present application provides a Ta-C composite coating, tetrahedral amorphous carbon Ta-C (Tetrahedral Amorphous Carbon) is a subclass of diamond-like carbon (DLC), which is composed of a high proportion of sp 3 hybrid carbon atoms (diamond-like bonding structure), and does not contain hydrogen. Unlike hydrogen-containing DLC (such as a-C:H), Ta-C is composed of only carbon atoms, which form an amorphous network structure through sp 3 and sp 2 hybrid bonds.
[0048] Figure 1 FIG. 1 is a schematic diagram of the structure of the Ta-C composite coating according to an embodiment of the present application. The composite coating is formed on a substrate 1, which can be a high-speed steel substrate, a stainless steel substrate, or a cast iron substrate, etc. The composite coating includes a transition layer 2 and a wear-resistant layer 3 which are sequentially stacked. Specifically, the transition layer 2 includes a Me layer 21, a MeN layer 22, a Me(W)N layer 23, and a MeWN layer 24, and the wear-resistant layer 3 includes a WC layer 31, a WC / Ta-C composite layer 32, and a Ta-C layer 33. Me is Cr or Ti. In an embodiment, the transition layer 2 includes a Cr layer, a CrN layer, a Cr(W)N layer, and a CrWN layer.
[0049] The Ta-C composite coating of the present application is formed on the substrate 1. For some substrates with relatively small hardness, a plating technology can be used to enhance the rigid support ability of the substrate material. For example, if the substrate is high-speed steel, precipitation hardening stainless steel, etc., no plating treatment is needed. If the substrate is other soft materials such as stainless steel, cast iron, etc., a plasma nitriding technology can be used. The plasma nitriding technology can ionize ammonia (NH3) molecules through direct current voltage glow discharge, and then sputter nitrogen ions to the surface of the substrate. The nitriding process has only 1 / 5 of the time of the gas nitriding process, and the nitriding temperature is significantly lower than that of the ordinary gas phase nitriding. The ion nitriding can be performed at 380℃, which can greatly reduce the thermal deformation of the substrate and is beneficial to the dimensional accuracy of the stable parts. The treated substrate does not need to be processed again. The surface of the nitriding layer of the plasma nitriding process has no white layer, and no special polishing is needed, and the subsequent coating deposition can be directly performed. The substrate 1 after the above substrate treatment step includes a flow substrate body 10 and an ion nitriding layer 11 on the surface thereof. The above substrate treatment step can avoid the phenomenon of poor adhesion between the substrate and the composite coating due to the over-fragility of the substrate surface, and has a good support effect on the composite coating. In an embodiment, the surface hardness of the ion nitriding layer 11 is greater than 1200HV, and the thickness of the ion nitriding layer is less than 100μm.
[0050] The W content of the Me(W)N layer of the Ta-C composite coating of the present application gradually increases in the thickness direction thereof. That is, the present application adopts a composite gradient transition layer structure on the surface of the substrate, the transition layer 2 gradually and gradiently transitions from the first Me layer 21 (metal layer) and the unit metal nitride phase (MeN layer 22) to the binary metal nitride phase (MeWN layer 24) through the W content gradient change of the Me(W)N layer 23, which can significantly improve the adhesion between the transition layer and the substrate. In an embodiment, the W content of the Me(W)N layer gradually increases from 0% to (70±5)% in the thickness direction of the Ta-C composite coating. The W content in the MeWN layer 24 is equal to the maximum W content in the Me(W)N layer, and accordingly, the W content of the MeWN layer is (70±5)%.
[0051] Further, the thickness of the transition layer 2 of the Ta-C composite coating is 35-45% of the thickness of the composite coating, wherein the thickness of the Me layer 21 is 5-10% of the thickness of the composite coating, the thickness of the MeN layer 22 is 5-15% of the thickness of the composite coating, the thickness of the Me(W)N layer 23 is 15-25% of the thickness of the composite coating, and the thickness of the MeWN layer 24 is 5-15% of the thickness of the composite coating. The addition of tungsten in the transition layer makes the linear expansion coefficient of the transition layer and the subsequent wear-resistant layer more similar, which can enhance the interlayer adhesion of the composite coating. In addition, the addition of tungsten can have a solid solution strengthening effect on the body-centered cubic lattice of MeN, and the shear strength and hardness are improved.
[0052] Figure 2 and Figure 3 The scanning electron microscope (SEM) image and energy dispersive spectrometer image of the Ta-C composite coating of an embodiment of the application, wherein Me is Cr, and the thickness of the a-C composite coating is about 3.5 μm. Taking the thickness of the Ta-C composite coating as 3-4 μm as an example, the thickness of the Me layer is 0.15-0.4 μm, the thickness of the MeN layer is 0.15-0.6 μm, the thickness of the Me(W)N layer is 0.45-1.0 μm, and the thickness of the MeWN layer is 0.15-0.6 μm.
[0053] The application provides a Ta-C composite coating (hydrogen-free diamond-like coating) with a novel structure, which realizes high wear resistance and high lubrication performance of the surface of a part. Compared with a conventional DLC coating, the Ta-C composite coating of the application adopts a composite transition layer structure and is transitioned to a Ta-C functional layer through phase gradient change, which greatly optimizes the mechanical properties of the transition layer. Further, the plasma nitriding technology is used before the deposition of the composite coating, which not only improves the support of the stainless steel substrate to the composite coating, but also significantly improves the bonding force between the substrate and the composite coating and the interlayer bonding force of the composite coating. Meanwhile, the Ta-C composite coating has better wear resistance than the conventional DLC, the friction coefficient is slightly lower than that of the DLC, the overall reliability is strong, and the part has a longer service life.
[0054] Similarly, the wear-resistant layer of the Ta-C composite coating of the present application can adopt the form of gradually transitioning from the metal carbide phase layer to the pure Ta-C layer, which can enhance the interlayer bonding force of the coating. Specifically, in the thickness direction of the Ta-C composite coating, the content ratio of Ta-C to WC of the WC / Ta-C composite layer 32 gradually increases. In practice, the phase gradient distribution trend of the WC / Ta-C composite layer 31 can be the sequential stacking of 90% WC-10% Ta-C layer, 50% WC-50% Ta-C layer, and 10% WC-90% Ta-C layer, that is, in the thickness direction of the composite coating, the content ratio of DLC to WC of the WC / Ta-C composite layer increases from 1 / 9 to 9. Further, the thickness of the wear-resistant layer 3 is 55-65% of the thickness of the composite coating, wherein the thickness of the WC layer 31 is 10-15% of the thickness of the composite coating, the thickness of the WC / Ta-C composite layer 32 is 15-25% of the thickness of the composite coating, and the thickness of the Ta-C layer 33 is 20-30% of the thickness of the composite coating. Taking the Ta-C composite coating with a thickness of 3-4 μm as an example, the thickness of the WC layer is 0.3-0.6 μm, the thickness of the WC / Ta-C composite layer is 0.45-1.0 μm, and the thickness of the Ta-C layer is 0.6-1.2 μm. Further, the Ta-C phase in the WC / Ta-C composite layer of the wear-resistant layer or the Ta-C phase in the Ta-C layer of the wear-resistant layer has a SP3 content of 20-30% and a SP2 content of 70-80%. 3 The carbon content ranges from 60% to 80%.
[0055] The wear-resistant layer of the Ta-C composite coating of the present application has a gradient increase in hardness and a gradient decrease in the thermal expansion coefficient along the thickness direction of the coating, so that the thermal expansion coefficients of the layers in the composite coating are more matched (see Table 1), thereby significantly reducing the thermal stress (internal stress) generated during the deposition of each layer, enhancing the bonding force between the composite coating and the substrate and between the layers of the composite coating, and preventing the peeling of the composite coating.
[0056] Table 1 shows the hardness and thermal expansion coefficient data of each functional layer of the Ta-C composite coating of the present application in the thickness direction thereof
[0057]
[0058] The present application also provides a preparation method of a Ta-C composite coating, which is suitable for preparing the aforementioned Ta-C composite coating and comprises the following steps:
[0059] Step S100: providing a substrate, and sequentially depositing Me layer, MeN layer, Me(W)N layer, MeWN layer and WC layer on the substrate by magnetron sputtering process. The Me layer (Ti layer or Cr layer) can be formed by depositing Me on the surface of the substrate by direct current magnetron sputtering of Ti target or Cr target in a protective atmosphere; the MeN layer can be formed by depositing MeN layer on the surface of the Me layer by direct current magnetron sputtering of Me target in a nitrogen-containing protective atmosphere; the Me(W)N layer and the MeWN layer can be formed by depositing Me(W)N layer and MeWN layer on the surface of the MeN layer by direct current magnetron sputtering of Me / W target in a nitrogen-containing protective atmosphere. In the above deposition process, the thickness and density of each layer can be controlled by adjusting and controlling the target power, target current, N2 flow rate, Ar flow rate, reaction pressure, deposition time, etc., so as to control the hardness and thermal expansion coefficient and other physical properties of each layer.
[0060] Step S200: depositing WC / Ta-C composite layer by magnetron sputtering process, specifically, depositing WC phase and Ta-C in the WC / Ta-C composite layer by magnetron sputtering of W / C target and C target, respectively.
[0061] Step S300: depositing Ta-C layer by arc ion plating process.
[0062] Before the step of depositing Me layer, the preparation method further comprises:
[0063] Step S010: treating the substrate by plasma nitriding process to form an ion nitriding layer on the surface of the substrate. The depth (thickness) and nitriding concentration of the ion nitriding layer formed on the surface of the substrate can be controlled by controlling the parameters of the plasma nitriding process, such as gas pressure, atmosphere ratio of NH3 and argon, NH3 flow rate, voltage, current, process temperature, process time, etc.
[0064] Further, in order to detect the Ta-C composite coating obtained by the preparation method of the present application, the performance of the Ta-C composite coating obtained by an embodiment, the existing DLC (a-C:H) coating (comparative example 1), and the stainless steel after nitriding treatment (comparative example 2) were tested.
[0065] Wherein, the same substrate is used, and the same brand of stainless steel substrate is used. The test friction mode is reciprocating, the coating is ground against cast iron material, and the coating and the grinding plate are in line contact. Dry friction: load 25N, rotation speed 430RPM, reciprocating distance 17mm, running time 20min, friction in air, record the friction coefficient and wear rate of the coating. The friction coefficient is taken from the average test value of two coating samples, and the wear rate is referred to the width value of the wear scar, which is taken from the average value of the width of the wear scar at four different positions. Dry friction mainly tests the wear resistance (anti-seizure and anti-fatigue wear) of the coating in harsh working conditions. Table 2 is the dry friction test results of the Ta-C composite coating obtained by the preparation method of the present application, comparative example 1 and comparative example 2.
[0066] Table 2 is the dry friction test results of the Ta-C composite coating obtained by the preparation method of the present application, comparative example 1 and comparative example 2
[0067]
[0068] From Table 2, it can be seen that the friction coefficient of the Ta-C composite coating of the present application is reduced by 4.2% compared with the conventional DLC (a-C:H) coating, the friction coefficient is similar to that of the DLC (a-C:H), and the wear rate is reduced by 18.4%. The friction coefficient of the Ta-C composite coating is reduced by 24.2% compared with the stainless steel nitriding layer, and the wear rate is reduced by 41.8%.
[0069] Although the embodiments of the present application have been shown and described above, it should be understood that the above embodiments are exemplary and should not be construed as limiting the present application, and those of ordinary skill in the art can make changes, modifications, replacements and variations to the above embodiments within the scope of the present application.
[0070] The above is a further detailed description of the present application in combination with specific preferred embodiments, and it cannot be considered that the specific implementation of the present application is limited to these descriptions. For those of ordinary skill in the art to which the present application belongs, without departing from the concept of the present application, a number of simple deductions or replacements can be made, which should be considered as falling within the protection scope of the present application.
Claims
1. A Ta-C composite coating, characterized in that: The composite coating is formed on a high-speed steel substrate, a stainless steel substrate or a cast iron substrate, and the composite coating comprises a transition layer and a wear-resistant layer stacked in sequence; The transition layer includes a Me layer, a MeN layer, a Me(W)N layer and a MeWN layer; The wear-resistant layer includes a WC layer, a WC / Ta-C composite layer and a Ta-C layer.
2. The Ta-C composite coating according to claim 1, characterized in that: The W content of the Me(W)N layer gradually increases in the thickness direction of the composite coating.
3. The Ta-C composite coating according to claim 1, characterized in that: In the thickness direction of the composite coating, the W content of the Me(W)N layer gradually increases from 0% to (70±5)%; and / or The W content of the MeWN layer is (70±5)%.
4. The Ta-C composite coating according to claim 1, characterized in that The thickness of the transition layer is 35-45% of the thickness of the composite coating; and / or The thickness of the Me layer is 5-10% of the thickness of the composite coating; and / or The thickness of the MeN layer is 5-15% of the thickness of the composite coating; and / or The thickness of the Me(W)N layer is 15-25% of the thickness of the composite coating; and / or The thickness of the MeWN layer is 5-15% of the thickness of the composite coating.
5. The Ta-C composite coating according to claim 1, characterized in that: In the thickness direction of the composite coating, the content ratio of Ta-C to WC in the WC / Ta-C composite layer gradually increases.
6. The Ta-C composite coating according to claim 1, characterized in that: In the thickness direction of the composite coating, the content ratio of Ta-C to WC in the WC / Ta-C composite layer increases from 1 / 9 to 9.
7. The Ta-C composite coating according to claim 1, characterized in that: The thickness of the wear-resistant layer is 55-65% of the thickness of the composite coating; and / or The thickness of the WC layer is 10-15% of the thickness of the composite coating; and / or The thickness of the WC / Ta-C composite layer is 15-25% of the thickness of the composite coating; and / or The thickness of the Ta-C layer is 20-30% of the thickness of the composite coating; and / or SP in the WC / Ta-C composite layer or the Ta-C phase in the Ta-C layer 3 The carbon content ranges from 60% to 80%.
8. The Ta-C composite coating according to claim 1, characterized in that: The thickness of the composite coating is 3-4 μm.
9. A method for preparing a Ta-C composite coating, characterized in that: The preparation method is applicable to preparing the Ta-C composite coating according to any one of claims 1 to 8, and the preparation method comprises the following steps: Providing a substrate, and sequentially depositing a Me layer, a MeN layer, a Me(W)N layer, a MeWN layer, and a WC layer on the substrate by a magnetron sputtering process; The WC / Ta-C composite layer was deposited using magnetron sputtering technology; The Ta-C layer was deposited using an arc ion plating process.
10. The method for preparing a Ta-C composite coating according to claim 9, characterized in that: Before the step of depositing the Me layer, the preparation method further comprises: The substrate is treated by a plasma nitriding process to form an ion nitriding layer on the surface of the substrate.